Outlaw's bride ebook - Copeland, Lori (The Western Sky., 2009)
Bestselling author Lori Copeland weaves together elements of a wonderful, classic Western romance with themes of forgiveness and grace. Falsely convicted of bank robbery, drifter Johnny McAllister is sent to a rehabilitation program in the home of a California judge. When he goes to Judge McMann's home, his aim is to be a model prisoner, hoping to be released early and return to his life's mission: to kill the man who wiped out his family 15 years before. He's planned for everything...except his encounter with Ragan, the beautiful and kind housekeeper, and with the generous folks of Barren Flats. But can Johnny let go of his anger and embrace a new life? One that would include Ragan as his bride? This tender story reveals how even the hard law of the land doesn't stand a chance when God's mercy and true love come to reside in a heart. Formerly titled The Bride of Johnny McAllister, rewritten for the inspirational market.